A new species of Herina Robineau-Desvoidy, 1830 (Diptera: Ulidiidae) from Turkey, with the key to species of oscillans group - Kameneva, Elena P.; Korneyev, Valery A. (Zootaxa, 2012)
Herina lazi sp. nov. from North Eastern Turkey is described. It shares small size, yellow face and femora, short oval flagellomere 1 of antenna, low oval eyes, and the apical brown spot on wing aligned to costal vein in cells r2+3 and r4+5 and shape of male and female genitalia with H. pseudoluctuosa Hennig, differing by details of the wing pattern and male genitalia. A key to species and diagnosis of Herina oscillans group of species are provided.